The Rise and Fall of the World's Largest Wine Exporter (And Its Institutional Legacy) - Giulia Meloni; Johan Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2013)
It is hard to imagine in the 21st global wine economy, but until 50 years ago Algeria was the largest exporter of wine in the world - and by a wide margin. Between 1880 and 1930 Algerian wine production grew dramatically. Equally spectacular is the decline of Algerian wine production: today, Algeria produces and exports little wine. This paper analyzes the causes of the rise and the fall of the Algerian wine industry. There was an important bi-directional impact between developments of the Algerian wine sector and French regulations. French regulations had a major impact on the Algerian wine industry. Vice versa, the growth of the Algerian wine industry triggered the introduction of important wine regulations in France at the beginning of the 20th century and during the 1930s. Important elements of these regulations are still present in the European Wine Policy today.
Keywords: K23; L51; N44; N54; Q13; 330; European agriculture; wine history; regulation; appellations; institutions; Weinbau; Weinhandel; Agrargeschichte; Wirtschaftsgeschichte; Algerien